Perceived roles of young adults kuyas towards their adolescent brothers and sisters - Aquino, Patricia Claudia Soriano (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This study sought to determine the perceived roles of ?kuyas? (older brothers), in sibling relationships. The nature of their interaction with their siblings in terms of indoor and outdoor activities done together and the content of their communication were investigated. The role perceptions of ?kuyas? to their younger siblings in the areas of their interaction with each other, academics, and peer relations were compared. The respondents were 30 ?kuyas? aged 21-28 years old who were randomly selected in Quezon City. Data were gathered through survey and interview and were analyzed using ANOVA, t-test (p-value=0.05), and thematic codes. ?Kuyas? perceived themselves as role models, second parents, and best friends to their younger siblings. Also, they did indoor and outdoor activities with their younger siblings regardless of their gender. ?Kuyas? were seen as concerned with their younger brothers regarding their friends and with their younger sisters when it comes to being in romantic relationships. Lastly, ?kuyas? were found to be equally concerned with their younger siblings‟ academics. ?Kuyas? therefore have roles that are not limited to their providing protection to their younger siblings as commonly assumed in the Philippine context.